Functional and radiological outcome in surgically managed posterior wall and column fractures of acetabulum - Rao, K. Nageswara; Soni, Ronak Dinesh; Nagesh, C.; Kumar, P. A. Shravan; Kumar, B. Arvind (International Journal of Research in Orthopaedics, 2021)
Background: The incidence of acetabular fractures has increased following road traffic accidents. The aim of the study is to evaluate functional and radiological outcome in surgically managed posterior wall and column fractures of acetabulum. Methods: This is a prospective study done at Nizam’s Institute of Medical Sciences, Hyderabad between May 2018 and May 2020. The sample size is 20 patients between the age group 18-60 years who presented to the hospital with closed posterior wall and/or column fractures of acetabulum with or without posterior dislocation of hip joint. Functional outcome is assessed by using the modified Merle D’ Aubigne Postel clinical grading system, radiological outcome by Matta et al and perioperative complication are assessed by retrospectively analyzing medical records and radiographics examination. Results: Functional outcome according to Merle D’ Aubigne and Postel score 16 patients (75%) showed good, 3 patients (20%) showed fair, 1 patient (5%) showed poor outcome. Radiological outcome according to Matta criteria, 16 patients (75%) showed excellent quality of joint reduction, 4 patients (25%) showed good quality of reduction of joint. There was significant correlation between anatomic reduction of the joint surface and functional outcome of the patient in our study (p value <0.05). Conclusions: Accurate joint reduction is of utmost importance in reduction of posterior wall or column fractures of acetabulum as posterior wall is the weight bearing zone. Functional outcome depends on fracture type, associated injuries, selection of patient, time between injury and surgery and postoperative rehabilitation.